Assessment of noise exposure in indoor firearm shooting range at police headquarters / Pragash Nair Guruvairapan - Pragash Nair, Guruvairapan (2018)
A research study similar to this is cannot be completed anyone alone. Contribution from varies people, in their own ways, have made this achievable. The appreciations to the all contributors are as follows. Primarily, my sincere gratitude is to my supervisors Dr. Jegalakshmi A/P Jewaratnam, for the countless support in completing this research studies, for their patience, motivation, enthusiasm, and immense knowledge. Their guidance helped me all the time of research and developing this project. Secondly, I would express my appreciation to Associate Prof. Dr. Ting Hua Nong and Dr. Tuan Zaharinie Binti Tuan Zahari for guiding me through Research Methodology course which was a stepping stone to this research. I would like to express my special thanks to the Royal Malaysian Police, for giving permission and support to conduct the research study at the indoor shooting range. Additionally, my sincere gratitude is to all shooting range staff and shooters who help me to complete the data collection within the time frame. Last but not least, my appreciation for my family, friends and anyone else for their constant encouragement and support to this project for success.